2014
DOI: 10.1093/jxb/eru131
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ANGULATA10 is required for thylakoid biogenesis and mesophyll development

Abstract: SummaryThis study characterized ANU10, a novel chloroplast protein encoded by a nuclear gene in Arabidopsis, which influences leaf and chloroplast shape and is required for thylakoid stacking and grana formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 89 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…Scale bars 2 mm that this might also be the case for other ANU genes that remain to be cloned. Indeed, this idea is validated by the recent cloning of ANU10, which was cloned using a conventional map-based approach and encodes a chloroplastlocalized protein that is required for normal grana stacking and leaf organogenesis (Casanova-Sáez et al 2014b). The anu1-1, anu4-1, anu9-1 and anu12-1 mutants described in this work turned out to be new alleles of the previously characterized SECA2, TOC33, NAP14 and CLPR1 genes (Jarvis et al 1998;Koussevitzky et al 2007;Shimoni-Shor et al 2010;Skalitzky et al 2011), all of which encode chloroplast-localized proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Scale bars 2 mm that this might also be the case for other ANU genes that remain to be cloned. Indeed, this idea is validated by the recent cloning of ANU10, which was cloned using a conventional map-based approach and encodes a chloroplastlocalized protein that is required for normal grana stacking and leaf organogenesis (Casanova-Sáez et al 2014b). The anu1-1, anu4-1, anu9-1 and anu12-1 mutants described in this work turned out to be new alleles of the previously characterized SECA2, TOC33, NAP14 and CLPR1 genes (Jarvis et al 1998;Koussevitzky et al 2007;Shimoni-Shor et al 2010;Skalitzky et al 2011), all of which encode chloroplast-localized proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Roots, shoots, and leaves longer than 5 mm were removed to obtain plant material enriched in leaf primordia and immediately frozen in liquid nitrogen. RNA purification and reverse transcription with random hexamers were carried out as described previously (Casanova-S aez et al, 2014). Three different biological replicates were used in triplicate reactions.…”
Section: Phenotypic Analyses and Morphometrymentioning
confidence: 99%
“…In line with this idea, the systematic cloning of genes identified in our large‐scale screen for ethyl methanesulfonate (EMS)‐induced mutants with abnormal leaf size and/or shape has evidenced that not few of such genes code for enzymes that catalyze steps in the biosynthesis pathways of arginine (Mollá‐Morales et al ., ), cellulose (Rubio‐Díaz et al ., ) or tetrapyrroles (Quesada et al ., ). The two most abundant phenotypic classes identified in this screen comprise mutants carrying alleles of nuclear genes that encode subunits of the cytosolic ribosome (Van Minnebruggen et al ., ; Horiguchi et al ., ; Casanova‐Sáez et al ., ) and chloroplast‐localized proteins, respectively (Casanova‐Sáez et al ., ; Mateo‐Bonmatí et al ., , ). Remarkably, many of the mutations in genes that appear to be housekeeping do not cause a mere growth retardation, but instead they cause specific phenotypes, as other authors have previously reported (Tsukaya et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in all these genes cause a pleiotropic phenotype that includes both defects in leaf size and shape and pale green pigmentation. The genes cloned so far include ANU1 , ANU4 , ANU9 , ANU10 and ANU12 (Casanova‐Sáez et al ., ; Mateo‐Bonmatí et al ., ), which in most cases encode proteins that contain an N‐terminal chloroplast transit peptide. We found our anu1 , anu4 , anu9 and anu12 mutants to be loss‐of‐function, viable alleles of the SECA2 , TRANSLOCON AT THE OUTER MEMBRANE OF CHLOROPLASTS 33 ( TOC33 ), NON‐INTRINSIC ABC PROTEIN 14 ( NAP14 ) and CLP PROTEASE PROTEOLYTIC SUBUNIT 1 ( CLPR1 ) genes (Jarvis et al ., ; Koussevitzky et al ., ; Shimoni‐Shor et al ., ; Skalitzky et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation